Studi Job Design dan Hubungannya dengan Work Overload pada Tenaga Kependidikan di Sekolah Dasar Se-Kota Palopo - Husni, Husni; Alauddin; Firmansyah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Elementary school education personnel face diverse work demands, so suboptimal job design has the potential to cause excessive workload (work overload). This condition can affect the effectiveness of task implementation and the well-being of education personnel. This study aims to analyze the condition of job design, the level of work overload, and the relationship between the two variables in elementary school education personnel in Palopo City. This study used a quantitative approach with a descriptive correlational design. The study population was 105 education personnel from 24 elementary schools, with a sample of 51 respondents selected through random sampling. Data were collected using a questionnaire via Google Form and analyzed with descriptive statistics and the Pearson Product Moment correlation test using SPSS version 20. The results showed that job design was in the high category, while work overload was in the moderate category. There was a positive and significant relationship between job design and work overload with a correlation coefficient of 0.457 and a significance of 0.000 (<0.05), indicating a moderate relationship. These findings indicate that job design characteristics need to be considered in managing the workload of education personnel in elementary schools.